PENGEMBANGAN UMPAN RAMAH LINGKUNGAN TERHADAP RAYAP TANAH (Coptotermes curvignathus Holmgren) - Fatmawati, Dewi; Muflihati, Muflihati (JURNAL HUTAN LESTARI, 2019)
Bait technology is the most effective, safe, and environmentally friendly way to termite control. This method was done by utilize attractants which have properties or aromas and able to invite termites to eat the bait. M. leucadendra leaves potentially used as an attractant. The matrix of bait material used as attractant to termites should contain high cellulose compound.. HVS paper and cardboard are materials with high cellulose compound, so they can used as bait. The aim of this study was to examine the efficacy of bait from M. leucadendra leaf mixture with waste paper to subterranean termites (Coptotermes curvignathus Holmgren) and to determine the optimal composition of the mixture of waste paper and M. leucadendra leaves which can be used as bait against termites. Tests are carried out with 2 methods, namely no choice test and multiple choice test. No-choice test was done by forced feeding, which was only one test sample in the test cup, with 55 termites (50 workers caste and 5 soldiers caste). Multiple choice test was done by giving food choices, which are all test samples for each composition in the test cup, with 165 termites (150 workers caste and 15 soldiers caste). The parameters observed were the weight loss of bait and mortality of termites. The results shows that the bait of the mixture of M. leucadendra leaves and paper waste in the no choice test and multiple choice test was effective used as bait to termites. Mixture of M. leucadendra: cardboard (60%: 40%) is the best composition bait for Subterranean C. curvignathus.Keyword: Baiting method, bioattractant, Coptotermes curvignathus, M. leucadendra leaves, wastepaper